Implementasi Kurikulum Cinta dalam Pembelajaran Bahasa Arab Madrasah - M. Isroul Laili (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2024)
The Love-Based Curriculum (LBC) is a pedagogical approach that emphasizes the internalization of the values of compassion, empathy, and spirituality as the foundation of the learning process. LBC is relevant for religious education because it seeks to transform the classroom into an environment that shapes the character and emotional maturity of students. This article aims to analyze the implementation of LBC in Arabic language learning in madrassas and describe its impact. The research method used is qualitative descriptive through literature study and analysis of curriculum policy documents and contemporary good practices, focusing on an analytical framework that identifies teaching practices that promote the values of 'Al-Mahabbah' (love) and rahmatan lil alamin. The results show that the integration of LBC in PBA has a significant impact on three aspects: (1) Increased learning motivation because a supportive classroom atmosphere reduces students' affective filters towards language difficulties; (2) Effective character strengthening, fostering empathy (ta'awun) and tolerance (tasamuh), in line with the values of the Rahmatan Lil Alamin Student Profile (PPRA); and (3) The creation of a very humanist and student-centered classroom atmosphere, where the role of the teacher shifts to a compassionate facilitator (murabbi). It is concluded that LBC is a transformative curriculum model that transforms Arabic learning from technical skills into a wholesome means of spiritual and social self-development. The implications of this study recommend LBC as a complementary approach to increase the effectiveness of the Independent Curriculum in madrassas